Identification and Functional Characterization of Plant MiRNA Under Salt Stress Shed Light on Salinity Resistance Improvement Through MiRNA Manipulation in Crops - Xu, Tao; Zhang, Long; Yang, Zhengmei; Wei, Yiliang; Dong, Tingting (Frontiers in Plant Science, 2021)
Salinity, as a major environmental stress, limits plant growth, development, and crop yield remarkably. Salinity, as a major environmental stress, limits plant growth, development, and crop yield remarkably. However, plant evolves its own defense system in response to salt stress. Recently, microRNA (miRNA) has been broadly studied and considered as an important regulator of plant salt stress response at the post-transcription level. In this review, we summarized the recent research progress on the identification, functional characterization, and regulatory mechanism of miRNA involved in salt stress, discussed the emerging manipulation of miRNA to improve crop salt resistance, and provided future direction for plant miRNA study under salt stress, suggesting that salinity resistance of crops could be improved by the manipulation of microRNA.